Exosomes derived from bone marrow mesenchymal stem cells reverse epithelial-mesenchymal transition potentially via attenuating Wnt/β-catenin signaling to alleviate silica-induced pulmonary fibrosis. (22nd November 2021) - Zhang, Enguo; Geng, Xiao; Shan, Shan; Li, Peng; Li, Shumin; Li, Wentao; Yu, Meili; Peng, Cheng; Wang, Shijun; Shao, Hua; Du, Zhongjun
Abstract: Pulmonary fibrosis induced by silica dust is an irreversible, chronic, and fibroproliferative lung disease with no effective treatment at present. BMSCs-derived exosomes (BMSCs-Exo) possess similar functions to their parent cells. In this study, we investigated the therapeutic potential and underlying molecular mechanism for BMSCs-Exo in the treatment of silica-induced pulmonary fibrosis. The rat model of experimental silicosis pulmonary fibrosis was induced with 1.0 mL of one-off infusing silica suspension using the non-exposed intratracheal instillation (50 mg/mL/rat). In vivo transplantation of BMSCs-Exo effectively alleviated silica-induced pulmonary fibrosis, including a reduction in collagen accumulation, inhibition of TGF-β1, and decreased HYP content. Treatment of BMSCs-Exo increased the expression of epithelial marker proteins including E-cadherin (E-cad) and cytokeratin19 (CK19) and reduced the expression of fibrosis marker proteins including α-Smooth muscle actin (α-SMA) after exposure to silica suspension. Furthermore, we found that BMSCs-Exo inhibited the expression of Wnt/β-catenin pathway components (P-GSK3β, β-catenin, Cyclin D1) in pulmonary fibrosis tissue. BMSCs-Exo is involved in the alleviation of silica-induced pulmonary fibrosis by reducing the level of profibrotic factor TGF-β1 and inhibiting the progression of epithelial-mesenchymal transition (EMT). Additionally, attenuation of the Wnt/β-catenin signaling pathway closely related to EMT may be one of the mechanisms involved in anti-fibrotic effects of exosomes.